Effect of Iron Applications on Grapevine Genotypes Growing in Different Calcareous Soils - OZDEMIR, GULTEKIN; TANGOLAR, SEMIH (Asian Journal of Chemistry, 2010)
In this study different grapevine genotypes having different resistance levels to CaCO3 were used as plant material. Genotypes were grown in pots including CaCO3 concentrations of 10, 30 and 50 %. For each medium, 4 different soil Fe applications were performed. These are: (i) 20 ppm Fe (as FeSO4) + farmyard manure (100 g/pot/5 kg soil), (ii) 20 ppm Fe (as Fe-EDDHA) (iii) 20 ppm Fe (as FeSO4) + citric acid (as 10 % percentage of applied FeSO4), (iv) control (soil without Fe). In order to determine the effects of applications on active and total iron concentrations of leaves were examined. As a result of the study, iron concentrations of all tested genotypes were decreased with increasing levels of CaCO3. Applications of Fe-EDDHA and FeSO4 + citric acid showed better results when all applications compared in respect of leaves active and total iron concentrations.